Species composition and abundance of small mammals on forest edge in southern Illinois in summer - Heske, Edward J.; Rodgers, Torrey W. (THERYA, 2022)
Relationships of mammals to habitat edges is a continuing concern for conservation as habitat fragmentation continues and ratios of edge to interior habitat increase. Mammal species that respond negatively to habitat edges may be at greater risk of extirpation, whereas species that are attracted to habitat edges may cause unanticipated ecological problems such as increased depredation of songbird nests. Proximity of contrasting habitats may also result in unique small mammal assemblages, including components of both habitats or providing opportunities for edge specialists (ecotonal effects). We compared the species composition of small mammals along live-trapping transects in forest edge, forest interior (both 100 m from edge and >1 km from edge), and the adjacent matrix (successional field or old field) in southern Illinois in summer 2003. All forest transects clustered together but differed from assemblages in either matrix type. Thus, we did not find an ecotonal effect on the forest side of the edge. The abundances of the three most common forest-dwelling species did not differ between forest edge and interior. However, there were more reproductive, adult female Peromyscus leucopus on transects in the forest interior, suggesting this may be higher-quality habitat at our study site, at least in summer. Edge effects have been reported for a variety of small mammal species, including P. leucopus in small (<2 ha) forest remnants and woodlots. We conclude that without supporting data one should not assume that edge effects are a consistent, general feature of small mammal abundance.